Validation of the Centrality of Pain Scale in Chinese-Speaking Patients with Painful Temporomandibular Disorders. Issue 4 (2nd January 2019) - Wang, Menghong; He, Songlin; Ji, Ping
Abstract: Objective: The present study aimed to validate the Centrality of Pain Scale (COPS) for use in Chinese patients with painful temporomandibular disorders (TMDs). Methods: The Centrality of Pain Scale was firstly translated and cross-culturally adapted following international guidelines. In total, 166 patients with TMD were recruited to complete the Chinese version of the COPS (COPS-C). In addition to the COPS-C, the patients were also administered the Pain Catastrophizing Scale (PCS) and the Pain Self-Efficacy Questionnaire (PSEQ). The reliability of the COPS-C was evaluated using internal consistency and test–retest methods. The construct validity of the COPS-C was evaluated using exploratory factor analysis (EFA). Convergent validity was determined by analyzing the correlations between COPS-C scores and the scores of the PCS and PSEQ. Results: Cronbach's alpha for the total COPS-C score was 0.942. The interitem correlations ranged from 0.356 to 0.901. The intraclass correlation coefficient values of the COPS-C ranged between 0.815 and 0.929. The results of the EFA indicated a one-factor solution for the measure, accounting for 70.4% of the total observed variance. The factor loadings of all items ranged from 0.713 to 0.917. Regarding convergent validity, the COPS-C had moderate correlations with the PCS and the PSEQ. Conclusions: The results provide initial evidence that the COPS-C is a reliable and valid measure. It can be used as a suitable instrument for Chinese patients with TMD.